Polymagmatic Glaciovolcanism: Cracked Mountain Tuya, Canadian Cascades - Harris, Martin A.; Russell, James K. (Frontiers in Earth Science, 2022)
Monogenetic volcanoes are characterized as having no temporal break in eruptive activity and are often assumed to have a simple (singular) magmatic plumbing system. However, recent studies on monogenetic systems have started to recover evidence of complexities within the magma-crustal dynamics. Here we investigate Cracked Mountain (CM), a 401 ± 38 ka glaciovolcanic basaltic landform in southwest, British Columbia, Canada. The volcano covers an area of ∼1.5 km2, has an eruptive volume of ∼0.18 km3, and comprises lapilli tuff, breccia, peperite, pillow and sheet lava, and dykes with no erosional surfaces present between the stratigraphic successions. The paleomagnetic signature of all volcanic lithofacies records a single-pole direction and, in conjunction with stratigraphic evidence, implies a monogenetic eruption. We establish that the Cracked Mountain volcano was fed by two separate crustally-stored magmas (i.e., polymagmatic), each characterized by a unique phenocryst assemblage indicative of different pre-eruptive storage conditions. The first mineral assemblage is an olivine-and-plagioclase phyric (OP) suite, and the second is an olivine-plagioclase-and-augite phyric (OPA) suite. The major-element geochemical compositions of the two petrographic suites vary slightly, with OPA samples higher in SiO2 and total-alkali contents than OP. The two magmas have similar rare earth (REE) trace element signatures, suggesting the same mantle source. We use thermodynamic modeling (Rhyolite-MELTS) to show that the OP suite derives from magma stored at depths <6 km (< 2 kbar) and temperatures of 1240–1155°C. In contrast, the OPA magmas crystallized at depths between 7–9 km (∼2–2.5 kbar) at 1,250–1,150°C prior to eruption. Both magmas are shown to be nearly “dry” having less than 0.5 H2O wt% in their respective systems. We use Pearce Element Ratios (PER) to show that the chemical variations within and between the two CM magmas are controlled solely by the crystal fractionation of two phenocryst assemblages that underwent syn-eruptive mixing. This study concludes that the polymagmatic plumbing system at Cracked Mountain shows similar complexities to other global investigations of monogenetic volcanoes. Lastly, we propose a causal link between the crustal dynamics of magma systems and the impact of crustal loading and unloading during cycles of glaciation.